Occupational safety and health in the Caribbean : a workers' education course (ILO. Caribbean Office Port of SpainTT, 1999)
Presents a course consisting of 11 units viz. occupational safety and health; the importance of occupational safety and health as an issue for trade unions in the Caribbean; identifying occupational safety and health problems in the Caribbean; the body and the workplace; noise; chemicals; ergonomics; methods of control; legislation and enforcement in the region; role of collective bargaining in occupational safety and health; and sources of information.
Keywords: OCCUPATIONAL SAFETY